Policy Analysis of Higher Education Financial Aid for Low-Income Communities: A Case Study of Tangerang City, Indonesia - Siti Aliyah; Muhammad Fedriyansyah; Hery Wibowo (Eduvest - Journal of Universal Studies, 2026)
Higher education is an important tool to improve the quality of human resources and support social mobility. However, many low-income people (MBRs) are hampered to access higher education due to cost limitations. Higher education assistance programs such as KIP Lecture are the solution to overcome these financial barriers. This study aims to analyze the policy of the higher education fee assistance program for the poor in Tangerang City using the Chambers social policy analysis framework. The method used was a descriptive qualitative approach, with data obtained through in-depth interviews with informants consisting of relevant officials in the Social Service, program managers, and beneficiaries. The results of the study show that this policy is effective in providing tuition assistance through direct transfers, but there are still challenges related to the sustainability of assistance, administrative difficulties in the verification process, and limitations in ensuring student graduation. Nevertheless, this policy has had a positive impact in reducing the burden of education costs for poor families. The study recommends improvements in terms of aid sustainability, strengthening long-term outcome indicators, and designing policies that are more responsive to the needs of beneficiaries, to ensure that the program can achieve its social goals optimally and sustainably.